Unusual Cutaneous Metastasis of Uterine Carcinosarcoma: A Case Report and Review of the Literature. (May 2016) - Clairwood, MariMeg; Yasuda, Mariko; Belazarian, Leah; Deng, April
Abstract : Abstract: Cutaneous metastasis of uterine cancer is rare and is often associated with late-stage disease. Most uterine malignancies are endometrial adenocarcinomas, but a small subset is uterine carcinosarcoma, also known as malignant mixed Mullerian tumors. Uterine carcinosarcomas are highly aggressive tumors with an average 5-year survival rate of 26%–34%. Metastases most commonly occur in the abdominal wall, lung, and bone. Cutaneous metastasis is exceedingly rare and may pose a diagnostic challenge. The authors report a 57-year-old woman with multiple subcutaneous nodules on the face and trunk. A biopsy revealed similar morphology and staining characteristics as the sarcomatous component of the primary uterine carcinosarcoma. Histopathological features and immunophenotypical characteristics of the metastatic tumor are detailed in comparison with the original tumor. A review of the literature is also provided.